The development of a foliar fungal pathogen does react to leaf temperature!. Issue 1 (4th February 2013) - Bernard, Frédéric; Sache, Ivan; Suffert, Frédéric; Chelle, Michaël
Summary: The thermal performance curve is an ecological concept relating the phenotype of organisms and temperature. It requires characterization of the leaf temperature for foliar fungal pathogens. Epidemiologists, however, use air temperature to assess the impacts of temperature on such pathogens. Leaf temperature can differ greatly from air temperature, either in controlled or field conditions. This leads to a misunderstanding of such impacts. Experiments were carried out in controlled conditions on adult wheat plants to characterize the response of Mycosphaerella graminicola to a wide range of leaf temperatures. Three fungal isolates were used. Lesion development was assessed twice a week, whereas the temperature of each leaf was monitored continuously. Leaf temperature had an impact on disease dynamics. The latent period of M. graminicola was related to leaf temperature by a quadratic relationship. The establishment of thermal performance curves demonstrated differences among isolates as well as among leaf layers. For the first time, the thermal performance curve of a foliar fungal pathogen has been established using leaf temperature. The experimental setup we propose is applicable, and efficient, for other foliar fungal pathogens. Results have shown the necessity of such an approach, when studying the acclimatization of foliar fungal pathogens.